Moment-angle relations in the initial time of contraction - Rousanoglou, E. N.; Herzog, W.; Boudolos, K. D. (International Journal of Sports Medicine, 2010)
Standard moment-angle relations are typically obtained for values at maximum of contraction. Muscle properties for contraction times, similar to the short times of powerful athletic activities, may be more important than muscle properties that are obtained at maximum (TMAX) of contraction. The research question was whether moment-angle relations obtained during the initial time course of contraction are linearly scaled reflections of moment-angle relations obtained at maximum of contraction. The isometric moment of the knee extensor and the electromyographic activity (EMG) of the knee extensor and flexor muscles were measured at 9 knee angles in 22 elite female track and field jumpers. Absolute moments (Nm), relative moments (%TMAX) and EMG integrals were determined at 30 ms, 50 ms, 150 ms and 200 ms from the onset of contraction and at maximum. For moment-angle relations obtained during the initial time course of contraction, there was a shift of the optimum knee angle to a more extended knee. During the initial time course of the contraction, %TMAX moment was greater near full knee extension. The EMG activity was the same across knee angles. The results may have important practical implications for muscular force evaluation for activities where maximum force production is coupled to a short activation time.